Technical-economic justification electric network 110 kV - Danylchenko, D. O.; Dryvetskyi, S. I.; Cherkashyna, V. V.; Shevchenko, S. Yu. (Aladdin-print, 2021)
The implementation of the course project for the course "Electrical Systems and Networks" is an important stage in the training of electric power specialists, which is due to the need for a comprehensive review and solution in these developments of a large group of technical and economic issues related to the operation of electric networks. The guidelines contain information about the order of the course project, the main ratios for performing electrical and technical and economic calculations, recommendations on the use of standard design solutions.
Keywords: methodical instructions; electric network; overhead lines; transformers